A synergetic strategy for an advanced electrode with Fe3O4 embedded in a 3D N-doped porous graphene framework and a strong adhesive binder for lithium/potassium ion batteries with an ultralong cycle lifespan. Issue 33 (8th August 2019) - Liu, Ying; He, Donglin; Tan, Qiwei; Wan, Qi; Han, Kun; Liu, Zhiwei; Li, Ping; An, Fuqiang; Qu, Xuanhui
Abstract : The chemical blowing strategy to fabricate novel Fe3 O4 nanoparticles decorated 3D N-doped porous graphene for high-performance LIBs and KIBs. Abstract : Fe3 O4 is considered to be a prospective anode material with superior capabilities for both lithium (Li) and potassium (K) storage, but its inferior conductivity and drastic volume change upon lithiation/potassiation bring great challenges to the realization of high capacity and stable cycling. Given these circumstances, we present a facile chemical blowing method to construct a three-dimensional N-doped porous graphene framework decorated with Fe3 O4 nanoparticles (Fe3 O4 /3DNPGF). In particular, the well-designed NPGF with massive pores and void space can not only buffer the volume variation of the embedded Fe3 O4 nanoparticles associated with Li + /K + insertion and extraction, but also reduce the steric effect, to enhance electron/ion transportation. In addition, the N-doping provides prolific active sites for electrochemical reactions and improves the electronic conductivity of the NPGF. More importantly, by introducing a novel binder material, a synergetic strategy was used to prepare robust electrodes with stronger adhesion between the active materials, conductive agents and binder material for greater tolerance towards volume change during cycling. Thus, the Fe3 O4 /3DNPGF electrodes demonstrated exceptional electrochemical activity in terms of high capacity, rate performance and prolonged lifespan in both lithium ion batteries (377.1 mA h g −1 at 10 A g −1 over 5000 cycles) and potassium ion batteries (154.6 mA h g −1 at 1 A g −1 over 500 cycles).